Penerapan Peraturan Menteri Keuangan Nomor 184/PMK.03/2015 Tentang Pemeriksaan Terkait Pengajuan Restitusi Pajak (Studi : CV. AA) - Ivan Jovi Hutauruk; Budiman Ginting; Sunarmi Sunarmi; Jelly Leviza (Jurnal Ilmiah Penegakan Hukum, 2021)
Taxes are state revenues that have a very important role in supporting the country's economy, which is used in state financing for the purpose of community welfare. In general, tax restitution relates to the right of the taxpayer to get a refund of the tax paid. The term tax restitution is contained in Law No. 16 of 2009 concerning General Tax Provisions (UU KUP). The purpose of this study is to answer legal issues related to tax refunds related to the regulation of the Minister of Finance. The research method used is normative juridical. Research result. Legal protection of the rights of taxpayers as can be interpreted as an effort to protect taxpayers from arbitrary acts of government in the field of taxation and regulation of administrative procedures so that taxpayers can receive their rights Conformity with the implementation of Regulation of the Minister of Finance Number 184 / PMK.03 / 2015 concerning Governance Examination method by exercising the authority of the tax authorities